Recombinase-based amplification coupled with lateral flow chromatography for the specific and sensitive detection and identification of Leishmania major in cutaneous leishmaniasis patients - Bel Hadj Ali, Insaf; Saadi-Ben Aoun, Yusr; Khammeri, Imen; Souguir, Hejer; Harigua-Souiai, Emna; Chouaieb, Hamed; Chakroun, Ahmed S.; Lemrani, Meryem; Kallel, Aicha; Kallel, Kalthoum; Haddad, Nabil; El Dbouni, Oussaima; et al. (Frontiers in Microbiology, 2025)
IntroductionCutaneous leishmaniases (CL), a wide range of cutaneous diseases caused by diverse species of Leishmania genus parasites, are among the most neglected infectious diseases. While they are non-fatal, CL are highly morbid with disfiguring lesions, which could be chronic, leaving lifelong unsightly scars; they are combined with psychological distress and social stigma. The efficiency of treatment highly depends on the infecting Leishmania species. Diagnosis is mainly based on microscopic direct examination (DE) of Giemsa-stained smears needing experienced microscopists. It can be laborious and time-consuming when the parasite load is low. DE is poorly sensitive and does not identify Leishmania species. So far, only DNA assays accurately identify the species. Despite their wide use for generic detection, PCR methods also require equipment and additional steps to identify causal Leishmania species. L. major is hyperendemic in many countries in Africa, the Middle East, and Asia, where other species co-occur with different endemicity levels according to the situations. This complicates disease management and treatment, particularly as distribution and epidemiology of leishmaniases remain poorly understood. Here, we aimed for a simple and rapid molecular diagnostic test to detect and identify L. major, a predominant CL causal species, which could be prone to become a control tool at the point of care, in endemic areas, using isothermal recombinase DNA amplification (recombinase polymerase amplification, RPA, or recombinase aided amplification, RAA) coupled to detection by the lateral flow (LF) chromatography on a PCRD cassette.MethodsTo develop an L. major species-specific RPA-LF assay, computational analysis of 70 Leishmania DNA targets, identified through bibliography and database searches, selected five targets. We designed and tested 7 primer pairs/probe sets to specifically amplify L. major DNAs. First, the primers were tested for species specificity and sensitivity using basic RPA chemistry. Then, to develop RPA-coupled LF detection, we shifted to the nfo chemistry.ResultsThis way, we retained one set for further investigation, which confirmed it is L. major species-specific. Tested on 86 human cutaneous samples, this selected set was able to detect 100% of L. major infections in confirmed CL patients. We did not observe any cross-reactivity with lesions due to L. infantum or L. tropica.